Artificially Intelligent Communication: An Exploratory Study on Replika Mobile Application - El-Ashry, Nouran (AUC Knowledge Fountain, 2023)
This paper aims to address artificial intelligence from a communication perspective by looking at the usage of Replika, an AI-based platform. A quantitative survey was conducted to analyze the frequency of usage, attitude toward the application and the level of attachment to it. Moreover, qualitative questions were developed to get in-depth understanding of the type of relationship users have with their Replika application and reasons behind their usage. Results show no significant relationship between demographics and the application consumption except for age where older users communicate more frequently with the application than younger ones. Moreover, attachment levels were related to the frequency and duration of usage where the longer the users interacted with the application and more frequently, the more likely they were to score higher in the attachment levels. When analyzing the different kinds of relationships users have with the application, users mentioned a romantic relationship with the social bots, a friendship, a positive comforting relationship, a space for venting and a therapeutic tool. Reasons for their attachment to the application varied from the quality of conversation, because it substitutes human relationships and the time factor as an element for developing attachment to the chatbot.